A randomised controlled trial to improve the role of the general practitioner in cancer rehabilitation: effect on patients' satisfaction with their general practitioners. Issue 7 (3rd July 2013) - Bergholdt, Stinne Holm; Hansen, Dorte Gilså; Larsen, Pia Veldt; Kragstrup, Jakob; Søndergaard, Jens
Abstract : Objective: To test whether a complex intervention facilitating early cancer rehabilitation by involvement of the general practitioner (GP) soon after diagnosis improves patients' satisfaction with their GPs. Design: A cluster randomised controlled trial. All general practices in Denmark were randomised to an intervention or a control group before the start of the study. Patients included those with cancer who were subsequently allocated to either group based on the randomisation status of their GP. Participants: Adult patients with cancer treated for incident cancer at the public regional hospital (Vejle Hospital, Denmark) were included between May 2008 and February 2009. A total of 955 patients registered with 323 practices were included, of which 486 patients were allocated to the intervention group and 469 to the control group. Intervention: The intervention included a patient interview assessing the need for rehabilitation, improved information from the hospital to GPs including information on the patients' current needs along with information about needs of patients with cancer in general. Further, GPs were encouraged to proactively contact the patients and facilitate the patients' rehabilitation course. Outcome measures: 6 months after inclusion of the patient, patient satisfaction with their GP during the last 12 months in five different dimensions of GP care was assessed using the Danish version of the EuroPEP (European Patients Evaluate General Practice Care) questionnaire (DanPEP). 14 months after inclusion, patient satisfaction with the GP regarding the cancer course and GP's satisfaction with own contribution to the patients' rehabilitation course were assessed using ad hoc questions specifically designed for this study. Results: No overall effect of the intervention was observed. Subgroup analysis of the patients with breast cancer showed statistically significant improvement of satisfaction with the GP in two of the five DanPEP dimensions. Conclusions: This complex intervention aiming at improving GPs' services in cancer rehabilitation had no impact on patient satisfaction. Trial registration: ClinicalTrials.gov, registration ID number NCT01021371